MiR-365-3p is a negative regulator in IL-17-mediated asthmatic inflammation - Wang, Weijia; Li, Ying; Fan, Jiaqi; Qu, Xiaoyan; Shang, Dong; Qin, Qiaohong; Xu, Tun; Hamid, Qutayba; Dang, Xiaomin; Chang, Ying; Xu, Dan (Frontiers in Immunology, 2022)
Background: Interleukin-17, the major proinflammatory cytokine secreted by Th17 cells, makes essential contribution to pathogenesis of severe asthma, while the detailed mechanisms, especially the involvement of microRNAs which are also important participants in asthma progression, remains largely unclear. Methods: In this study, we established a house dust mite (HDM) extract-induced murine asthmatic models and the miRNA expression in the lung tissues of mice were profiled by miRNA microarray assay. The effect of miR-365-3p on IL-17-dominated inflammation was examined by qRT-PCR, ELISA and immunoblotting analysis. The involvement of ARRB2 as target gene of miR-365-3p was verified by overexpression or RNA interference. Results: HDM extract-induced asthmatic inflammation was proved to be IL17-dominated and screened out miR-365-3p to be the only miRNA exclusively responsive to IL-17. miR-365-3p, whose expression was significantly downregulated upon IL-17 stimulation, was demonstrated to exert remarkable anti-inflammatory effect to decrease IL-17-provoked inflammatory cytokines (KC/IL-8 and IL-6) in both airway epithelial cells and macrophages of murine and human origins, verifying its universal antagonizing activity against IL-17-initiated inflammation across the two species. ARRB2 was characterized as the key target of miR-365-3p to negate IL-17-induced inflammatory cytokines. Conclusion: Taken together, our data supported the notion that miR-365-3p, which was diminished by IL-17 in murine and human asthmatic pathogenesis, functioned as an essential negative mediator in IL-17-stimuated inflammatory response by targeting ARRB2, which would shed new light to the understanding and therapeutics thereof of severe asthma.